Efisiensi Pemberian Air Pada Jaringan Irigasi Way Bini Kecamatan Waeapo Kabupaten Buru Provinsi Maluku - Said Ar Assagaf; Charles Silahooy; Pieter J Kunu; Silwanus Talakua; Rudi Soplanit (Agrologia, 2016)
Dams irrigation system is important facility to ensure the water availability during rice cultivation. The aim of this study was to verify the condition of Way Bini irrigation system in providing irrigation water and water distribution system to meet the needs of rice cultivation in Savana Jaya Village, Waeapo Subdistrict, Buru District. The research used survey method. The results showed that the irrigation water debit required for appropriate rice cultivtion was 677.16 L/sec (0.68 m3/sec) which was smaller than that of the Way Bini dam; 750 L / s (0.75 m3 / s), while the efficiency of the irrigation water requirement was 70% which was categorized as good to excellent.